The Racialization of the Indigeneity of Others - Roque, Ricardo (2020)
Racial conceptions pervaded modern colonial regimes of power throughout Southeast Asia. Scholars working today on colonial histories in this region would hardly contest this statement. European imperial expansionism and European racial imaginaries are each part of the same political field; they share a common history and as such they should be examined together. In this vein, in recent decades there has been increasing interest in how the production and circulation of race constructs—whether evocative of purity or mixture, of an elusive whiteness, or of primitive aboriginality/ies, for example—might frame, even construct, colonial and national regimes of power. In particular, scholarly interest has been growing in the historical study of the so-called racial sciences, a plastic designation under which one may encompass a variety of selfproclaimed scientific knowledge practices—from medicine to (physical) anthropology, the nineteenth-century science of race par excellence